CLOUD SERVICES IN EDUCATION - Seydametova, З.С.; Seytvelieva, С.Н. (Journal of Information Technologies in Education (ITE), 2011)
We present the on-line services based on cloud computing, provided by Google to educational institutions. We describe the own experience of the implementing the Google Apps Education Edition in the educational process. We analyzed and compared the other universities experience of using cloud technologies.